Personal exposure to static and time-varying magnetic fields during MRI procedures in clinical practice in the UK - Batistatou, Evridiki; Mölter, Anna; Kromhout, Hans; van Tongeren, Martie; Crozier, Stuart; Schaap, Kristel; Gowland, Penny A.; Keevil, Stephen F.; de Vocht, Frank (BMJ Publishing Group, 2015)
Background: MRI has developed into one of the most important medical diagnostic imaging modalities, but it exposes staff to static magnetic fields (SMF) when present in the vicinity of the MR system, and to radiofrequency and switched gradient electromagnetic fields if they are present during image acquisition. We measured exposure to SMF and motion-induced time-varying magnetic fields (TVMF) in MRI staff in clinical practice in the UK to enable extensive assessment of personal exposure levels and variability, which enables comparison to other countries. Methods: 8 MRI facilities across National Health Service sites in England, Wales and Scotland were included, and staff randomly selected during the days when measurements were performed were invited to wear a personal MRI-compatible dosimeter and keep a diary to record all procedures and tasks performed during the measured shift. Results: 98 participants, primarily radiographers (71%) but also other healthcare staff, anaesthetists and other medical staff were included, resulting in 149 measurements. Average geometric mean peak SMF and TVMF exposures were 448 mT (range 20–2891) and 1083 mT/s (9–12 355 mT/s), and were highest for radiographers (GM=559 mT and GM=734 mT/s). Time-weighted exposures to SMF and TVMF (GM=16 mT (range 5–64) and GM=14 mT/s (range 9–105)) and exposed-time-weighted exposures to SMF and TVMF (GM=27 mT (range 11–89) and GM=17 mT/s (range 9–124)) were overall relative low—primarily because staff were not in the MRI suite for most of their shifts—and did not differ significantly between occupations. Conclusions: These results are comparable to the few data available from the UK but they differ from recent data collected in the Netherlands, indicating that UK staff are exposed for shorter periods but to higher levels. These data indicate that exposure to SMF and TVMF from MRI scanners cannot be extrapolated across countries.